WALLABY pilot survey: first look at the Hydra I cluster and ram pressure stripping of ESO 501−G075. Issue 2 (14th May 2021) - Reynolds, T N; Westmeier, T; Elagali, A; Catinella, B; Cortese, L; Deg, N; For, B-Q; Kamphuis, P; Kleiner, D; Koribalski, B S; Lee-Waddell, K; Oh, S-H; et al.
ABSTRACT: We present results from neutral atomic hydrogen (H i ) observations of Hydra I, the first cluster observed by the Widefield ASKAP L-band Legacy All-sky Blind Survey (WALLABY) on the Australian Square Kilometre Array Pathfinder. For the first time, we show that WALLABY can reach its final survey sensitivity. Leveraging the sensitivity, spatial resolution, and wide field of view of WALLABY, we identify a galaxy, ESO 501−G075, that lies near the virial radius of Hydra I and displays an H i tail. ESO 501−G075 shows a similar level of morphological asymmetry as another cluster member, which lies near the cluster centre and shows signs of experiencing ram pressure. We investigate possible environmental processes that could be responsible for producing the observed disturbance in the H i morphology of ESO 501−G075. We rule out tidal interactions, as ESO 501−G075 has no nearby neighbours within ∼0.34 Mpc. We use a simple model to determine that ram pressure can remove gas from the disc at radii r ≳ 25 kpc. We conclude that, as ESO 501−G075 has a typical H i mass compared to similar galaxies in the field and its morphology is compatible with a ram pressure scenario, ESO 501−G075 is likely recently infalling into the cluster and in the early stages of experiencing ram pressure.